Popular Culture as Political Communication. An Introduction - van Zoonen, Liesbet (Javnost-The Public, 2000)
Popular culture is becoming ever more important to political communication and political understanding. In this article popular culture is defined as schematic in its syntagmatic and paradigmatic structures, individualised and gendered. These three features are shown to underlie and guide the performance of popular culture as political communication, especially when popular culture appears as political fiction in movies and television series; when popular culture is used as a political stage for political actors who take on standard personas; and when popular culture functions as a political practice in itself, for instance, in talk shows and popular music. These three ways in which popular culture functions as a form of political communication are elaborated in the various contributions in this special issue to which this article provides the introduction.